Bacillary Dysentery - jefri irawan; Meilisa Hidayah Putri; Rani Himayani; Ratna Dewi Puspita Sari (Medula, 2021)
Gastrointestinal infection due to amoeba is one of the causes of diarrhea which appears to be a public health problem with a high incidence in the community. Bacillary dysentery/shigellosis has become a major cause of morbidity and mortality in children in developing countries, and is also an important cause of morbidity in industrialized countries. Shigella sp. is a diarrheal pathogen that is closely related to Escherichia coli. The pathogen was named by Kiyoshi Shiga, who in 1898 identified the most virulent strain of shigella, Shigella dysenteriae, as the causative agent of shigellosis. Shigella spp. is a Gram-negative bacillus from the family Enterobacteriaceae. Therefore, the aim of this literature review is to further review the management of bacillary dysentery. Shigellae is transmitted by the faecal-oral route or through ingestion of contaminated food and water. This research is a literature review involving as many as 10 library sources with the keywords used, namely 'management and shigellosis' with the year published between 2012 - 2021. Abstracts and full text of the journal are read and examined, then an analysis of the contents contained in the research objectives is carried out and research results/findings. Results. Various studies have shown over the last few decades, Shigella spp. have undergone mutations, developing mechanisms to damage cell processes in the gastrointestinal tract. Therefore, innovative methods and appropriate management are needed to prevent antibiotic resistance in the treatment of shigellosis.